Bidirectional Glenn on cardiopulmonary bypass: A comparison of three techniques. Issue 5 (9th April 2017) - Talwar, Sachin; Kumar, Manikala Vinod; Nehra, Ashima; Malhotra Kapoor, Poonam; Makhija, Neeti; Sreenivas, Vishnubhatla; Choudhary, Shiv Kumar; Airan, Balram
Abstract: Objective: To analyze the intraoperative and early results of the bidirectional Glenn (BDG) procedure performed on cardiopulmonary bypass (CPB) using three different techniques. Methods: Between September 2013 and June 2015, 75 consecutive patients (mean age 42 ± 34.4 months) undergoing BDG were randomly assigned to either technique I: open anastomosis or technique II: superior vena cava (SVC) cannulation or technique III: intermittent SVC clamping. We monitored the cerebral near infrared spectrophotometry (NIRS), SVC pressure, CPB time, intensive care unit (ICU) stay, and neurocognitive function. Results: Patients in technique III had abnormal lower NIRS values during the procedure (57 ± 7.4) compared to techniques I and II (64 ± 7.5 and 61 ± 8.0, P  = 0.01). Postoperative SVC pressure in technique III was higher than other two groups (17.6 ± 3.7 mmHg vs. 14.2 ± 3.5 mmHg and 15.3 ± 2.0 mmHg in techniques I and II, respectively = 0.0008). CPB time was highest in technique II (44 ± 18 min) compared to techniques I and III (29 ± 14 min and 38 ± 16 min, P  = 0.006), respectively. ICU stay was longer in technique III (30 ± 15 h) compared to the other two techniques (22 ± 8.5 h and 27 ± 8.3 h in techniques I and II, respectively = 0.04). No patient experienced significant neurocognitive dysfunction. Conclusion: All techniques of BDG provided acceptable results. The open technique was faster and its use in smaller children merits consideration. The technique of intermittent clamping should be used as a last resort.